"The Only True People" Linking Maya Identities Past and Present - bin Beyyette, Bethany J. (University Press of Colorado, 2017)
In The Only True People, a multidisciplinary group of archaeologists, linguists, ethnographers, ethnohistorians, and epigraphers evaluate views of Maya history and prehistory in order to more accurately characterize the unique nature of the people known as the Maya by exploring the construction of their identities in the past and the present. Each author evaluates what makes identifiable sociocultural units, or "ethnicities," distinctive, investigating ethnicity at a number of Maya sites across different time periods: from the northern reaches of the Yucatan to the Southern Periphery, and from the Classic period to the modern day. The volume challenges the notion of an ethnically homogenous "Maya people" within their region and chronology, and the authors explain how their work contributes to the definition of "ethnicity" for ancient Maya society.